Lysyl oxidase-like 4 promotes the invasiveness of triple-negative breast cancer cells by orchestrating the invasive machinery formed by annexin A2 and S100A11 on the cell surface - Takahashi, Tetta; Tomonobu, Nahoko; Kinoshita, Rie; Yamamoto, Ken-ichi; Murata, Hitoshi; Komalasari, Ni Luh Gede Yoni; Chen, Youyi; Jiang, Fan; Gohara, Yuma; Ochi, Toshiki; Ruma, I Made Winarsa; Sumardika, I Wayan; et al. (Frontiers in Oncology, 2024)
Background: Our earlier research revealed that the secreted lysyl oxidase-like 4 (LOXL4) that is highly elevated in triple-negative breast cancers (TNBCs) acts as a catalyst to lock annexin A2 on the cell membrane surface, which accelerates invasive outgrowth of the cancer through the binding of integrin-β1 on the cell surface. However, whether this machinery is subject to the LOXL4-mediated intrusive regulation remains uncertain.Methods: Cell invasion was assessed by a transwell-based assay; protein-protein interactions by an immunoprecipitation-western blot technique and immunocytochemistry; and plasmin activity in the cell membrane by gelatin zymography.Results: We revealed that cell-surface annexin A2 acts as a receptor of plasminogen via interaction with S100A10, a key cell surface annexin A2-binding factor, and S100A11. We found that the cell surface annexin A2/S100A11 complex leads to mature active plasmin from bound plasminogen, which actively stimulates gelatin digestion, followed by increased invasion.Conclusions: We have refined our understanding of the role of LOXL4 in TNBC cell invasion: namely, LOXL4 mediates upregulation of annexin A2 at the cell surface; the upregulated annexin 2 binds S100A11 and S100A10; and the resulting annexin A2/S100A11 complex acts as a receptor of plasminogen, readily converting it into active-form plasmin and thereby enhancing invasion.